2022
DOI: 10.3389/fevo.2022.794495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Temperatures on the Development and Reproduction of Sitobion miscanthi From Six Different Regions in China

Abstract: The increase in temperature caused by global warming has greatly impacted plant growth and pest population dynamics worldwide, especially for wheat aphids. In this study, Sitobion miscanthi individuals from six geographic populations located in different wheat-producing areas in China were compared with regard to their growth, development, survival, and reproductive under different temperature conditions (17, 22 and 27°C). A population life-table analysis and a correlation analysis between geographic factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…It is customary for entomologists and pest management specialists to quantify temperature effects on the life‐history traits of pests and newly invaded species through laboratory experiments. In fact, the pest management and entomological literature is replete with such studies (e.g., Correa et al, 2021; Karpicka‐Ignatowska et al, 2021; Sun et al, 2022), meaning that the information required for quantifying the thermal niche of invasive species is likely to be widely available.…”
Section: Discussionmentioning
confidence: 99%
“…It is customary for entomologists and pest management specialists to quantify temperature effects on the life‐history traits of pests and newly invaded species through laboratory experiments. In fact, the pest management and entomological literature is replete with such studies (e.g., Correa et al, 2021; Karpicka‐Ignatowska et al, 2021; Sun et al, 2022), meaning that the information required for quantifying the thermal niche of invasive species is likely to be widely available.…”
Section: Discussionmentioning
confidence: 99%
“…We found that field experimental warming more than doubled population densities of both main aphid species, S. avenae and R. padi , in accordance with results from previous studies (Han et al., 2018, 2019; Wang et al., 2021). This may be because warming shortens the developmental period of insects, enabling them to complete more generations faster and, therefore, reach higher population densities (Sun et al., 2022; Thomson et al., 2010; Tobin et al., 2008; Wang & Ma, 2022). Aphids would be especially likely to reach high population densities faster through their continuous clonal reproductive mode under mild and warm temperatures (Gilabert et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the effects of increased temperature on H. axyridis predation in conditions of resource limitation, we assessed how experimental warming in the laboratory affected the functional response of H. axyridis to the two most abundant aphid species, R. padi and S. avenae . Wheat aphids were reared on wheat variety Hengguan 35 in separate cages in an insectary under 19°C, 70 ± 5% RH, and a 16L:8D photoperiod, which are the optimal conditions for aphid rearing in the insectary (Park et al., 2017; Sun et al., 2022; Wang et al., 2021). Individuals of H. axyridis were provided by the Institute of Plant Protection, Beijing Academy of Agricultural and Forestry Sciences and reared in the laboratory on a M. japonica aphid diet on broad bean, under 25°C, 70 ± 5% RH, and a 16L:8D photoperiod, which are the optimal conditions for H. axyridis rearing in the insectary (Wang et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…These variations may be due to the different host plants (especially cultivars) offered to the larvae as well as the available nutrient content and nutritional quality of the host plants [ 6 , 34 , 89 ]. The differences in chemical compounds, along with factors other than the temperature, such as insect genetic makeup, geographic origin, and environmental conditions (relative humidity and photoperiod) [ 90 , 91 ], emphasized that information regarding the nutritional value of the host plants offered is significant in order to develop viable and applicable management strategies against polyphagous insects, because the economic standing of polyphagous insects is mediated by the nutritional quality and by the relative abundance of the host plants. In this study, the S. litura eggs could not hatch or complete their development at the higher extreme temperature (40 °C) on either the host plants or the artificial diet.…”
Section: Discussionmentioning
confidence: 99%